The Effect of Different Drying Method on the Physico-Chemical Characteristics of Senduduk Fruit Powder (Melastoma Malabathricum L) and its Application as Natural Colorant in Food - Desy Cristiana; Rina Yenrina; Cesar Welya Refdi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
This study aimed to determine the effect of different drying methods on the physical and chemical characteristics of Senduduk fruit powder determine the best drying method in producing then applied as a natural dye to food. This study used an exploratory method with three treatments (drying method with an oven dryer, vacuum oven, and sun dryer). The result showed that the use of different drying methods resulted in different physical and chemical characteristics of the senduduk fruit powder and the best drying method in this study was using a vacuum oven with physical and chemical characteristics, that is the yield of 15.57%, ºHue 45.27, time dissolving time 60.08 seconds, insoluble part 4.34%, water content 8,76%, drying time 8 hours, ash content 2.36%, antioxidant activity 67.44%, anthocyanin content 45.52 (mg/L), organoleptic test on cookies, ice cream and pudding products with the addition of senduduk powder as a natural colorant, namely the cookies product obtained an average value of 3.2 (Neither like nor dislike